KONSEP KELUARGA MASLAHAH DALAM PANDANGAN NYAI MUDA PONDOK PESANTREN ALI MAKSUM KRAPYAK YOGYAKARTA - Lailata, Afida; Ibrahim, Malik (UIN Sunan Kalijaga Yogyakarta, 2014)
Marriage is one of the Sunnah of the Messenger and the religious advice.Marriage in the Qur’an referred to as mitsaqan ghalizhan (grandagreement). However, today in most families, the marriage was impressedmerely as a means of getting descent and distribution of sexual libidoor impingement sheer lust. So the role of the family is considered notfunctioning as it should. Therefore, building a maslahah family is acentral element in Islam, because the family unit is the major joints ofsociety. According to the views of young Nyai from Boarding of KrapyakYogyakarta, in building maslahah family is not only a form of support inan effort to mature age of marriage, birth control or guidance of familysupport, but also efforts to improve the lives of the family concerned.There are two things to look for in this article, namely, first, about theconcept of maslahah family by young Nyai from Boarding of KrapyakYogyakarta. Secondly, the Islamic legal review of the concept of maslahahfamily in view of young Nyai from Boarding of Krapyak Yogyakarta.This paper is a research field with normative juridical approach. Whereis the primary source was obtained through interviews with three younghousekeeper at boarding school Krapyak Yogyakarta in 2013.